Maximizing the Value of Donated Medical Equipment in Resource-limited Settings: The Roles of Donors and End-users - Williams, Dinsie B.; Kohler, Jillian Clare (CMBES Proceedings, 2016)
Background: Medical technologies, such as medical devices, are essential to healthcare delivery yet, in some settings there is a pervasive shortage that severely limits the capacity of clinicians to assess, diagnose, treat, monitor, and prevent diseases. Transnational funders have taken on the responsibility of providing funds for almost 80% of medical equipment in countries with severe shortages, yet 70% of equipment goes unused and abandoned. This means that, in the best-case scenario, for every dollar spent on donations, at least 62.5 cents goes to waste. The question then arises about why funders continue to support such magnitudes of waste in settings where demand for improving healthcare is so high. Objective: This study aims to understand the roles of transnational donors and end-users in defining and implementing equipment donation and funding policies in Accra, Ghana. The study will explore how existing policies on equipment donation incorporate transparency and accountability. The study will also identify opportunities for optimizing the value of donations and minimizing waste for the end-users. Methodology: We will develop a case study based on a review of policy and guideline documents, and on survey data and interviews of technicians, nurses, physicians, and staff of funding organizations. Potential Impact: This study will contribute to the growing body of research at the intersection of health policy, transnational philanthropy, and development. Findings from this study will be useful to policymakers in improving utility (or value) of medical equipment, and subsequently enhancing health benefits.